Flow Characteristics in an Open Channel Flume Based on Bed Slope Variation at the Civil Engineering Laboratory of Universitas Lancang Kuning - Marlaily Idris; Virgo Trisep Haris; Hendri Rahmat; Fitridawati Soehardi (Journal of Infrastructure and Civil Engineering, 2026)
This study aims to analyze the effect of bed slope variation on flow characteristics in an open channel flume at the Civil Engineering Laboratory of Universitas Lancang Kuning. The research was conducted experimentally using a laboratory flume with constant discharge conditions. Three slope variations were applied, namely 0.001, 0.003, and 0.005. The observed parameters include flow velocity and flow depth. In addition, the Froude number was calculated to determine the type of flow regime. The results indicate that increasing the bed slope leads to an increase in flow velocity from 0.20 m/s to 0.33 m/s. Meanwhile, the flow depth tends to decrease as the slope increases. The calculated Froude number ranges from 0.201 to 0.343, indicating that the flow regime remains in subcritical conditions. These results provide empirical insight into the relationship between bed slope and hydraulic characteristics in open channel flow and can serve as reference data for hydraulic laboratory experiments.